Peran Spiritualitas Sebagai Strategi dalam Mengelola Stres Akademik Bagi Mahasiswa Semester Akhir di UIN Sunan Ampel Surabaya - Machfud, Mochammad (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2025)
This study aims to uncover the role of spirituality as a strategy in managing academic stress in final semester students, especially when facing the pressure of final assignments, exams, and graduation preparation. The theory used involves the concept of spirituality as a search for the meaning of life according to Pargament and academic stress as a psychological response to the imbalance of demands and abilities according to Busari. The research method used was descriptive qualitative with data collection through semi-structured interviews with four students who met the criteria, namely those who used spirituality to deal with academic stress. The results of the analysis showed that spiritual practices such as prayer, meditation, and self-reflection contributed significantly to reducing anxiety, providing inner peace, and improving students' adaptability. In addition, spirituality helps students find meaning in academic challenges and strengthens their mental resilience. This study concluded that spirituality is an effective holistic strategy in supporting the mental well-being and academic success of final semester students. The recommendation from this study is the integration of spirituality practices in student support programs to create better emotional balance.